Tools and Challenges in Digital Humanities for Cultural Heritage in Spain - Abia, Antoni García; Davalos, Pablo; Notredame, Juan Satorras (Journal of Humanities and Social Sciences (JHASS), 2023)
Digital humanities have emerged as a transformative field, leveraging technology to preserve and analyze cultural artifacts. In Spain, the integration of digital tools into cultural heritage projects has significantly enhanced documentation, analysis, and public engagement. This study explores the tools and methodologies employed in these initiatives, evaluates their effectiveness, and identifies challenges and opportunities. Conducted throughout 2023, the research adopts a mixed-methods approach involving 150 respondents, including scholars, heritage professionals, and policymakers, with data collected from institutions such as the National Library of Spain and prominent cultural sites like the Alhambra. The findings highlight the widespread use of digital imaging (85%), 3D modeling (78%), virtual reality (65%), and geospatial mapping (70%), each contributing uniquely to heritage preservation and accessibility. While the effectiveness of these tools is evident, challenges such as the lack of standardized methodologies, insufficient funding, and limited training persist. Opportunities for interdisciplinary collaboration and the integration of emerging technologies like AI suggest a promising future. This study underscores the need for standardized practices, increased funding, and enhanced training programs to fully realize the potential of digital humanities. Future research should focus on scaling these initiatives and exploring innovative applications of advanced technologies to further enhance the preservation of Spain's cultural legacy.